Increasing Socially Significant Behaviors for Children with Autism Using Synchronous Reinforcement - Stephany K. Stordahl; Joseph H. Cihon; Shahla Alai-Rosales; Jesus Rosales-Ruiz (MDPI AG, 2023)
In some types of reinforcement schedules, a reinforcer is presented or given to the child and interacted with continuously while a target behavior is occurring. Previous researchers have used this type of reinforcement as an assessment tool and to study basic reinforcement processes. However, little research has explored how to effectively use these schedules to reinforce socially important responses in applied settings. The current study analyzed the implementation of synchronous reinforcement in a nonconcurrent multiple baseline across participants. Several interventionists implemented synchronous reinforcement with four children with autism across a variety of responses and reinforcers. The results indicated that delivering social, audio/visual, and tangible stimuli on a synchronous schedule resulted in increased durations of targeted (e.g., social skills and motor skills) and nontargeted (e.g., approach, social bids, and speed) measures across all children. Recommendations regarding reinforcer and response selection in implementing synchronous schedules in applied settings are provided.